A method for manufacturing a non-stripping cloth-pultruded plate
Patent Information
- Application Number
- CN202311626234.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-30
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2043-11-30
AI Technical Summary
In the current pultrusion sheet production process, stearate-based release agents form a film on the sheet surface, which hinders the bonding performance of subsequent resin injection. Furthermore, the use of release cloth leads to instability in the production process and increased costs.
Modified internal release agent M012 and internal release agent M011 are compounded and added directly to the adhesive solution through in-situ curing technology to form an oleophobic and hydrophilic interface and chemically bond with the injection resin, achieving rapid demolding and strong adhesion.
It enables rapid demolding and strong bonding of pultruded sheets, reduces the process difficulties and costs caused by the use of release cloth, and improves production efficiency and material utilization.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of pultruded sheet preparation technology, and in particular to a method for preparing a demolding-free pultruded sheet. Background Technology
[0002] The main beam (also known as the beam cap or main beam) of a wind turbine blade is the main load-bearing component or the main structural component of the blade. Currently, most wind turbine blades are manufactured using a pultrusion process to produce plates of a certain thickness (usually 5 μm thick, mainly including pultruded glass plates and pultruded carbon plates) to make the main beam.
[0003] In the pultrusion process, a certain amount of internal release agent needs to be added to the adhesive to facilitate demolding. However, traditional internal release agents are mostly stearates. After the release agent enters the mold cavity with the adhesive, the stearates precipitate into a gel-like substance and migrate to the surface of the sheet as curing progresses, forming a thin film with high release properties at the mold cavity cross-section, thus enabling smooth demolding of the pultruded sheet. After the sheet cures, the migration of stearate-based release agents does not stop and continues to slowly migrate to the sheet surface over time. However, this film hinders the adhesion of the resin to the surface of the pultruded sheet during the subsequent wind turbine blade injection process.
[0004] To ensure effective bonding between pultruded sheets and blades during subsequent infusion processes, GM applies release fabric to the upper and lower surfaces of the pultruded sheets during molding, removing it later in the finishing process. This process creates a roughened surface on the pultruded sheet, increasing the contact area between the resin and the sheet surface. This improves the interfacial properties between the pultruded sheet and the fiber cloth after infusion, preventing delamination and displacement caused by insufficient adhesion between the pultruded sheet and the fiber cloth during subsequent use. Therefore, release fabric plays a crucial role in increasing the surface roughness of pultruded sheets and blades during production. However, the use of release fabric in pultruded sheet production presents several challenges: unstable edge distance, edge binding, wrinkles, inclusions, and debonding, significantly compromising production process stability. Furthermore, the use and subsequent removal of release fabric increases the manufacturing cost of pultruded sheets.
[0005] Therefore, in order to address the above problems, the present invention urgently needs to provide a method for preparing a demolding-free extruded plate. Summary of the Invention
[0006] The purpose of this invention is to provide a method for preparing a demolding-free pultruded sheet. This method addresses the technical problems in the prior art where stearates are used as internal release agents in the pultruded sheet production process. After the pultruded sheet is cured, the film formed by the release agent on the pultruded sheet hinders the adhesion of the resin to the surface of the pultruded sheet during the subsequent wind turbine blade injection process. Furthermore, while release cloths are used to create a certain degree of roughness on the surface of the pultruded sheet, they suffer from unstable edge distances, edge binding, wrinkles, inclusions, and debonding, posing significant challenges to the stability of the production process.
[0007] The present invention provides a method for preparing a demolding-free extruded plate, comprising the following steps: According to the weight parts, 100 parts of glycidyl ether epoxy resin, 80-90 parts of acid anhydride curing agent, 0-2 parts of accelerator, 10-20 parts of toughening agent, 0.5-2 parts of modified internal release agent M012 and 0.5-2 parts of internal release agent M011 are mixed and mechanically stirred to obtain a uniformly dispersed adhesive solution. Prepreg is obtained by impregnating continuous reinforcing fibers with an adhesive solution. The prepreg is sequentially extruded, molded, cured, pulled, and cut to obtain a demolding-free extruded sheet. M012 is a multi-branched polymer with oleophobic functional groups and -COO-ester bonds; The internal release agent M011 is at least one of acrylic acid, acrylic acid derivatives, or maleic acid.
[0008] Preferably, the molecular structure of M012 is as follows:
[0009] Wherein, X is one or more of -CH=CH2, -CH3, -NH2, RCO-, halogen atom or -SO3H.
[0010] Preferably, the glycidyl ether epoxy resin is one or more of bisphenol A type epoxy resin, bisphenol F type epoxy resin, and bisphenol S type epoxy resin.
[0011] Preferably, the anhydride curing agent includes one or more of tetrahydrophthalic anhydride, hexahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, trimellitic anhydride, tung oil anhydride, methylnadic anhydride, or maleic anhydride.
[0012] Preferably, the continuous reinforcing fiber is one or both of glass fiber and carbon fiber.
[0013] Preferably, the mass ratio of glycidyl ether epoxy resin to modified internal release agent M012 is 100:1.5.
[0014] Preferably, the accelerator is one or more of 2-ethyl-4-methylimidazole, 2-methylimidazoleurea, or 1-methyl-3-ethylimidazole.
[0015] Preferably, the toughening agent is one or more of polyether, polyetheramine, core-shell polymer or nitrile rubber.
[0016] Preferably, mechanical stirring is used, and the temperature of mechanical stirring is controlled at 40-80℃ to obtain a uniformly dispersed adhesive solution.
[0017] Preferably, the adhesive solution accounts for 20-40% of the mass of the prepreg.
[0018] Preferably, the adhesive comprises 30% of the mass of the prepreg.
[0019] The method for preparing a demolding-free extruded plate provided by this invention has the following advantages compared with the prior art: 1. In the in-situ curing method for preparing demolding-free pultruded sheets provided by this invention, a modified internal release agent MO12 is selected, wherein X is a modified release functional group segment in the molecular structure of the MO12 internal release agent, which is one or more of -CH=CH2, -CH3, -NH2, RCO-, halogen atom, or -SO3H. It exhibits typical oleophobic and hydrophilic properties and migrates to the resin surface during the resin's thermal cross-linking and curing stage, effectively reducing the interfacial tension on the sheet surface, thereby forming an interface with a certain demolding effect and achieving rapid pultrusion of the sheet. Demolding; furthermore, MO11 was added, and MO11 and MO12 were compounded. The large number of -COO- ester bonds in the molecular structure of the release agent in MO12 are resin anchoring functional groups. They add to the -C=C- in the molecular structure of MO11 through addition polymerization. The -COOH in the molecular structure of MO11 is reactive. When the pultruded sheet is cured and laid into the cavity of the wind turbine blade and subjected to the infusion process, the -COOH reacts with the infusion resin to form chemical bonds. Therefore, a strong interfacial adhesion can be formed on the surface of the pultruded sheet.
[0020] 2. The self-made modified internal release agent M012 in this invention replaces the traditional release agent. Because the release functional groups of the prepared M012 macromolecule are modified and optimized, it gives the product excellent release performance while minimizing the impact on adhesion. In the subsequent blade laying and injection process, the injection resin exhibits excellent adhesion performance on the surface of the board, thereby eliminating the need for the use of release cloth in the pultrusion board production process. This directly avoids the process problems caused by the use of release cloth in the pultrusion board production process, and also eliminates the post-processing steps caused by tearing off the release cloth, greatly saving the raw material production cost, labor and management cost caused by using release cloth.
[0021] 3. The pultruded sheet preparation method proposed in this invention involves directly compounding the modified internal release agent M012 and internal release agent M011 in the adhesive solution. This eliminates the need to adjust the production process of the pultruded sheet, facilitating engineering production. It also provides convenient conditions for subsequent process improvements and production speed-ups for pultruded glass sheets and pultruded carbon sheets. The production speed can reach 1.0 m / min, achieving a significant improvement in production efficiency.
[0022] 4. The modified release agent of this invention has no effect on the surface effect of the sheet material, providing convenient conditions for online visual monitoring system and online non-destructive testing technology in the pultruded sheet production process. It allows the sheet material to be inspected to be fully exposed to the testing system, improving the identification accuracy of the testing system, effectively avoiding the occurrence of batch defects, and greatly improving the utilization rate of raw materials.
[0023] 5. The in-situ curing technology used in this invention assembles the composite materials together in liquid form, and then uses high temperature and high pressure to cure them. The curing process can be completed in situ within the material, thus avoiding the disassembly process in traditional methods and greatly improving the curing efficiency of the material. The internal release agent M012 is directly added to the resin liquid. During the curing process of pultrusion epoxy resin, the two react chemically, completing the demolding of the sheet and introducing reactive -COOH into the subsequent injection resin, enhancing the adhesion between the subsequent injection resin and the sheet surface. This eliminates the need for laying release cloth during the production of pultruded sheets and the need to remove the release cloth before the pultruded sheets enter the inner cavity of the wind turbine blade for vacuum injection. It realizes the production of pultruded sheets without release cloth, reduces production steps and material consumption, and saves production costs. Detailed Implementation
[0024] The technical solution of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0025] The present invention provides a method for preparing a demolding-free extruded plate, comprising the following steps: According to the weight parts, 100 parts of glycidyl ether epoxy resin, 80-90 parts of acid anhydride curing agent, 0-2 parts of accelerator, 10-20 parts of toughening agent, 0.5-2 parts of modified internal release agent M012 and 0.5-2 parts of internal release agent M011 are mixed and mechanically stirred to obtain a uniformly dispersed adhesive solution. Prepreg is obtained by impregnating continuous reinforcing fibers with an adhesive solution. The prepreg is sequentially extruded, molded, cured, pulled, and cut to obtain a demolding-free extruded sheet. M012 is a multi-branched polymer with oleophobic functional groups and -COO-ester bonds; The internal release agent M011 is at least one of acrylic acid, acrylic acid derivatives, or maleic acid.
[0026] Preferably, the molecular structure of M012 is as follows:
[0027] Wherein, X is one or more of -CH=CH2, -CH3, -NH2, RCO-, halogen atom or -SO3H.
[0028] Specifically, glycidyl ether epoxy resins are one or more of bisphenol A type epoxy resins, bisphenol F type epoxy resins, and bisphenol S type epoxy resins.
[0029] Specifically, the anhydride curing agent includes one or more of tetrahydrophthalic anhydride, hexahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, trimellitic anhydride, tung oil anhydride, methylnadic anhydride, or maleic anhydride.
[0030] Specifically, the continuous reinforcing fiber is one or both of glass fiber and carbon fiber.
[0031] Specifically, the mass ratio of glycidyl ether epoxy resin to modified internal release agent M012 is 100:1.5.
[0032] Specifically, the accelerator is one or more of 2-ethyl-4-methylimidazole, 2-methylimidazoleurea, or 1-methyl-3-ethylimidazole.
[0033] Specifically, the toughening agent is one or more of polyether, polyetheramine, core-shell polymer or nitrile rubber.
[0034] Specifically, mechanical stirring is performed at a temperature controlled between 40-80℃ to obtain a uniformly dispersed adhesive solution.
[0035] Specifically, the adhesive solution accounts for 20-40% of the mass of the prepreg.
[0036] Specifically, the adhesive comprises 30% of the mass of the prepreg.
[0037] The present invention provides a method for preparing demolding-free pultruded sheets using in-situ curing, employing a modified internal release agent MO12. X is a modified release functional group segment in the MO12 internal release agent molecule, which is one or more of -CH=CH2, -CH3, -NH2, RCO-, halogen atoms, or -SO3H. It exhibits typical oleophobic and hydrophilic properties, migrating to the resin surface during the resin's thermal cross-linking and curing stage. This effectively reduces the interfacial tension on the sheet surface, thereby forming an interface with a certain demolding effect, achieving rapid demolding of the pultruded sheet. Furthermore, MO11 was added, and MO11 and MO12 were compounded. The large number of -COO- ester bonds in the molecular structure of the release agent in MO12 serve as resin anchoring functional groups. They undergo addition polymerization with -C=C- in the molecular structure of MO11. The -COOH in the molecular structure of MO11 is reactive. When the pultruded sheet is cured and laid into the cavity of the wind turbine blade and subjected to the infusion process, the -COOH reacts with the infusion resin to form chemical bonds. Therefore, a strong interfacial adhesion can be formed on the surface of the pultruded sheet.
[0038] The self-made modified internal release agent M012 in this invention replaces the traditional release agent. Because the release functional groups of the prepared M012 macromolecule are modified and optimized, it endows the product with excellent release performance while minimizing the impact on adhesion. In the subsequent blade laying and injection process, the injection resin exhibits excellent adhesion performance on the surface of the board. This eliminates the need to use release cloth in the pultrusion board production process, directly avoiding the process problems caused by using release cloth in the pultrusion board production process. At the same time, it eliminates the post-processing steps caused by tearing off the release cloth, which greatly saves the raw material production cost, labor and management cost caused by using release cloth.
[0039] The pultrusion board preparation method proposed in this invention involves directly compounding modified internal release agent M012 and internal release agent M011 in the adhesive solution, which eliminates the need to adjust the production process of pultruded boards, facilitating engineering production. At the same time, it provides convenient conditions for subsequent process improvement and production speed-up of pultruded glass boards and pultruded carbon boards, with a production speed of up to 1.0 m / min, achieving a significant improvement in production efficiency.
[0040] The modified release agent of this invention has no effect on the surface effect of the sheet material, providing convenient conditions for online visual monitoring systems and online non-destructive testing technology in the pultruded sheet production process. It allows the sheet material to be inspected to be fully exposed to the inspection system, improving the identification accuracy of the inspection system, effectively avoiding the occurrence of batch defects, and greatly improving the utilization rate of raw materials.
[0041] The in-situ curing technology employed in this invention assembles composite materials together in liquid form, then cures them using high temperature and high pressure. This allows the curing process to be completed within the material itself, avoiding the disassembly and assembly process of traditional methods and significantly improving curing efficiency. The internal release agent M012 is directly added to the resin liquid, and a chemical reaction occurs between the two during the curing of the pultruded epoxy resin. This not only completes the demolding of the sheet but also introduces reactive -COOH groups into the subsequent resin injection, enhancing the adhesion between the resin and the sheet surface. This eliminates the need for laying release cloth during pultruded sheet production and for removing the release cloth before vacuum injection into the wind turbine blade cavity. This achieves demolding cloth-free production of pultruded sheets, reducing production steps and material consumption, and saving production costs.
[0042] Example 1 In-situ curing is used to prepare demolding-free Braided extruded sheets. The specific steps are as follows: 101) According to the weight parts, mix 100 parts of glycidyl ether epoxy resin, 80 parts of acid anhydride curing agent, 1 part of accelerator, 10 parts of toughening agent, 0.5 parts of modified internal release agent M012, and 0.5 parts of internal release agent M011. Mix mechanically and control the temperature of mechanical stirring at 40℃ to obtain a uniformly dispersed adhesive solution. 102) Continuous reinforcing fibers are impregnated with an adhesive solution to obtain a prepreg. 103) The prepreg is sequentially extruded, molded, cured, stretched, and cut to obtain a demolding-free extruded sheet; M012 is a multi-branched polymer with oleophobic functional groups and -COO-ester bonds.
[0043] Specifically, the molecular structure of M012 is as follows:
[0044] Among them, the substituents X are -CH=CH2, -CH3 and -NH2, with -CH=CH2 accounting for 25% of the total number of substituents X, -CH3 accounting for 55% of the total number of substituents X, and -NH2 accounting for 20% of the total number of substituents X.
[0045] Specifically, glycidyl ether epoxy resins are bisphenol A type epoxy resins.
[0046] Specifically, the anhydride curing agent is tetrahydrophthalic anhydride.
[0047] Specifically, the continuous reinforcing fiber is glass fiber.
[0048] Specifically, the accelerator is 2-ethyl-4-methylimidazole.
[0049] Specifically, the toughening agent is polyether.
[0050] Specifically, the adhesive comprises 20% of the mass of the prepreg.
[0051] Example 2 The in-situ curing method is used to prepare demolding-free extruded sheets. The specific steps are as follows: 201) According to the weight parts, 100 parts of glycidyl ether epoxy resin, 90 parts of acid anhydride curing agent, 1.5 parts of accelerator, 15 parts of toughening agent, 1 part of modified internal release agent M012 and 1 part of internal release agent M011 are mixed and mechanically stirred at a temperature of 80°C to obtain a uniformly dispersed adhesive solution. 202) The continuous reinforcing fibers are impregnated with an adhesive solution to obtain a prepreg. 203) The prepreg is sequentially extruded, molded, cured, stretched, and cut to obtain a demolding-free extruded sheet; M012 is a multi-branched polymer with oleophobic functional groups and -COO-ester bonds.
[0052] The molecular structure of M012 in this embodiment is the same as that in Example 1. The difference is that the substituents X are -CH=CH2, -CH3 and RCO-. -CH=CH2 accounts for 35% of the total number of substituents X, -CH3 accounts for 45% of the total number of substituents X, and RCO- accounts for 25% of the total number of substituents X.
[0053] Specifically, glycidyl ether epoxy resins are bisphenol F type epoxy resins.
[0054] Specifically, the anhydride curing agent is hexahydrophthalic anhydride.
[0055] Specifically, the continuous reinforcing fiber is carbon fiber.
[0056] Specifically, the accelerator is 2-methylimidazole.
[0057] Specifically, the toughening agent is polyetheramine.
[0058] Specifically, the adhesive comprises 25% of the mass of the prepreg.
[0059] Example 3 In-situ curing is used to prepare demolding-free Braided extruded sheets. The specific steps are as follows: 301) By weight, mix 100 parts of glycidyl ether epoxy resin, 85 parts of acid anhydride curing agent, 1.5 parts of accelerator, 20 parts of toughening agent, 1.5 parts of modified internal release agent M012 and 1.5 parts of internal release agent M011, and mechanically stir at a temperature of 60°C to obtain a uniformly dispersed adhesive solution. 302) The continuous reinforcing fibers are impregnated with an adhesive solution to obtain a prepreg. 303) The prepreg is sequentially extruded, molded, cured, stretched, and cut to obtain a demolding-free extruded sheet; The molecular structure of M012 in this embodiment is the same as that in Example 1. The difference is that the substituent X is -CH3, -NH2 and halogen atom. -CH3 accounts for 25% of the total number of substituent X, -NH2 accounts for 55% of the total number of substituent X, and halogen atom accounts for 20% of the total number of substituent X.
[0060] Specifically, glycidyl ether epoxy resins are one or more types of bisphenol S-type epoxy resins.
[0061] Specifically, the anhydride curing agent includes one or more of tetrahydrophthalic anhydride, hexahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, trimellitic anhydride, tung oil anhydride, methylnadic anhydride, or maleic anhydride.
[0062] Specifically, the continuous reinforcing fiber is a mixture of glass fiber and carbon fiber.
[0063] Specifically, the accelerator is 1-methyl-3-ethylimidazole.
[0064] Specifically, the toughening agent is a mixture of core-shell polymer and nitrile rubber.
[0065] The adhesive accounts for 40% of the mass of the prepreg.
[0066] Example 4 In-situ curing is used to prepare demolding-free Braided extruded sheets. The specific steps are as follows: 401) According to the weight parts, mix 100 parts of glycidyl ether epoxy resin, 95 parts of acid anhydride curing agent, 1 part of accelerator, 20 parts of toughening agent, 2 parts of modified internal release agent M012 and 2 parts of internal release agent M011, and mechanically stir. The temperature of mechanical stirring is controlled at 70℃ to obtain a uniformly dispersed adhesive solution. 402) The continuous reinforcing fibers are impregnated with an adhesive solution to obtain a prepreg. 403) The prepreg is sequentially extruded, molded, cured, stretched, and cut to obtain a demolding-free extruded sheet; M012 is a multi-branched polymer with oleophobic functional groups and -COO-ester bonds.
[0067] The molecular structure of M012 in this embodiment is the same as that in Example 1. The difference is that the substituent X is -CH3, -NH2 and halogen atom. -CH3 accounts for 25% of the total number of substituent X, -NH2 accounts for 55% of the total number of substituent X, and halogen atom accounts for 20% of the total number of substituent X.
[0068] Specifically, the glycidyl ether epoxy resin is a mixture of bisphenol F type epoxy resin and bisphenol S type epoxy resin.
[0069] Specifically, the anhydride curing agent is a mixture of methyl nadic anhydride and maleic anhydride.
[0070] Specifically, the continuous reinforcing fiber is glass fiber.
[0071] Specifically, the accelerator is 2-ethyl-4-methylimidazole.
[0072] Specifically, the toughening agent is polyether.
[0073] Specifically, the adhesive comprises 30% of the mass of the prepreg.
[0074] Comparative Example In-situ curing was used to prepare demolding-free Braided extruded boards. 100 parts epoxy resin, 90 parts acid anhydride curing agent, 1 part accelerator, 20 parts heat-increasing agent, and 0.5 parts traditional internal release agent are thoroughly mechanically stirred to obtain a uniformly dispersed adhesive solution. Glass fibers are then rationally arranged according to the yarn threading diagram, impregnated with the adhesive, pre-formed, extruded and molded, cured, pulled, cut, and finished.
[0075] The epoxy resin is a bisphenol A type epoxy resin.
[0076] The curing agent is tetrahydrophthalic anhydride.
[0077] The accelerator is 2-ethyl-4-methylimidazole.
[0078] The toughening agent is polyether.
[0079] The adhesive solution accounts for 20% of the mass of the prepreg.
[0080] The interfacial mechanical properties of Examples 1, 2, 3, 4 and the comparative example were tested using a DSC-214 testing machine from Netzsch Instruments GmbH, Switzerland. The test parameters were: heating rate 20 ℃ / min, temperature range 30℃~150 ℃. The interfacial mechanical properties of the fiber-reinforced materials, such as interlaminar shear strength (ILSS - two layers of pultruded plate + sandwich fabric) and tensile shear strength, were tested in accordance with international standards ISO 14130 and DIN EN 1465, respectively. The test results are shown in Table 1.
[0081] Table 1. Interfacial mechanical properties and glass transition temperature (Tg) of extruded sheets prepared by in-situ curing without demolding Example Lamellar shear strength (MPa) Tensile shear strength (MPa) Tg (°C) Example 1 51.6 26.1 115.1 Example 2 53.1 27.2 115.7 Example 3 52.9 26.9 116.2 Example 4 53.6 28.3 114.7 Comparative Example 38.6 18.2 115.2 Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a demolding-free extruded sheet, characterized in that: Includes the following steps: According to the weight parts, 100 parts of glycidyl ether epoxy resin, 80-90 parts of acid anhydride curing agent, 0-2 parts of accelerator, 10-20 parts of toughening agent, 0.5-2 parts of modified internal release agent M012 and 0.5-2 parts of internal release agent M011 are mixed and mechanically stirred to obtain a uniformly dispersed adhesive solution. Prepreg is obtained by impregnating continuous reinforcing fibers with an adhesive solution. The prepreg is sequentially extruded, molded, cured, pulled, and cut to obtain a demolding-free extruded sheet. M012 is a multi-branched polymer with oleophobic functional groups and -COO-ester bonds; the internal release agent M011 is at least one of acrylic acid, acrylic acid derivatives, or maleic acid; the molecular structure of M012 is as follows: Wherein, X is one or more of -CH=CH2, -CH3, -NH2, RCO-, halogen atom or -SO3H.
2. The method for preparing the demolding-free extruded plate according to claim 1, characterized in that: Glycidyl ether epoxy resins are one or more of bisphenol A type epoxy resin, bisphenol F type epoxy resin, and bisphenol S type epoxy resin.
3. The method for preparing the demolding-free extruded plate according to claim 1, characterized in that: Anhydride curing agents include one or more of tetrahydrophthalic anhydride, hexahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, trimellitic anhydride, tung oil anhydride, methylnadic anhydride, or maleic anhydride.
4. The method for preparing the demolding-free extruded plate according to claim 1, characterized in that: The continuous reinforcing fiber is one or both of glass fiber and carbon fiber.
5. The method for preparing the demolding-free extruded plate according to claim 1, characterized in that: The mass ratio of glycidyl ether epoxy resin to modified internal release agent M012 is 100:1.
5.
6. The method for preparing the demolding-free extruded plate according to claim 1, characterized in that: The accelerator is one or more of 2-ethyl-4-methylimidazole, 2-methylimidazole, or 1-methyl-3-ethylimidazole.
7. The method for preparing the demolding-free extruded plate according to claim 1, characterized in that: The toughening agent is one or more of polyether, polyetheramine, core-shell polymer or nitrile rubber.
8. The method for preparing the demolding-free extruded plate according to claim 1, characterized in that: Mechanical stirring, with the temperature controlled at 40-80℃, yields a uniformly dispersed adhesive solution.
9. The method for preparing the demolding-free extruded plate according to claim 1, characterized in that: The adhesive solution accounts for 20-40% of the mass of the prepreg.
Citation Information
Patent Citations
Epoxy resin composition, cured dry film, cured product and printed circuit board
CN110642998A
Epoxy resin batch for pultrusion of composite material and preparation method of epoxy resin batch
CN114907548A
Thermoplastically moldable compositions
CN1210871A
